Limb-darkened radiation-driven winds from massive stars - Curé, Michel (2012)
We calculated the influence of the limb-darkened finite-disk correction factor in the theory of radiation-driven winds from massive stars. We solved the one-dimensional m-CAK hydrodynamical equation of rotating radiation-driven winds for all three known solutions, i.e., fast, Ω-slow, and δ-slow. We found that for the fast solution, the mass-loss rate is increased by a factor of 10%, while the terminal velocity is reduced about 10%, when compared with the solution using a finite-disk correction factor from a uniformly bright star. For the other two slow solutions, the changes are almost negligible. Although we found that the limb darkening has no effects on the wind-momentum-luminosity relationship, it would affect the calculation of synthetic line profiles and the derivation of accurate wind parameters.